In the tall, tall grass - Fleming, Denise, 1950- (New York : Holt, 1995)
Rhymed text (crunch, munch, caterpillars lunch) presents a toddler's view of creatures found in the grass from lunchtime till nightfall, such as bees, ants, and moles.
Elem. School Library Collection
School Library Journal starred
Wilson's Children
1.5
K-3.
K-3
Keywords: Animals -- Fiction; Stories in rhyme; Animals -- Fiction; Stories in rhyme